PEACE JOURNALISM TRANSMISSIONS IN CASE OF PAPUA STUDENTS BY "NU ONLINE" - Lukman Hakim (al-Balagh : Jurnal Dakwah dan Komunikasi, 2021)
This article aims to analyze how NU online frames a Papuan case from 19 to 20 August 2019. NU Online's coverage is analyzed for news content and its efforts to understand, interpret, and implement peace journalism to alleviate tensions and conflicts. The concept of peace journalism is important to study and implement comprehensively. It seeks to be objective in presenting information and not provocative to minimize the potential for subsequent conflict. Entman framing analysis is used as the research method because it can see the reality constructs done by media by examining the process for selection and highlighting a particular aspect. Therefore, the main data were taken from NU Online coverage related to a Papuan college student's case. Through the content, the framing of NU Online editorial could be seen. Meanwhile, the conclusionof this research was that NU Online, as the official media of Pengurus Besar Nahdlatul Ulama had a coverage orientation that emphasized harmony and peace. Angle choice, title drafting, diction use, and source choice highlighted that NU Online focused on the aim to alleviate as well as support conflict solving.